Cost‐effectiveness analysis of epilepsy surgery in a controlled cohort of adult patients with intractable partial epilepsy: A 5‐year follow‐up study. (5th September 2016) - Picot, Marie‐Christine; Jaussent, Audrey; Neveu, Dorine; Kahane, Philippe; Crespel, Arielle; Gelisse, Philippe; Hirsch, Edouard; Derambure, Philippe; Dupont, Sophie; Landré, Elizabeth; Chassoux, Francine; Valton, Luc; et al.
Summary: Objective: Despite its well‐known effectiveness, the cost‐effectiveness of epilepsy surgery has never been demonstrated in France. We compared cost‐effectiveness between resective surgery and medical therapy in a controlled cohort of adult patients with partial intractable epilepsy. Methods: A prospective cohort of adult patients with surgically remediable and medically intractable partial epilepsy was followed over 5 years in the 15 French centers. Effectiveness was defined as 1 year without a seizure, based on the International League Against Epilepsy (ILAE) classification. Clinical outcomes and direct costs were compared between surgical and medical groups. Long‐term direct costs and effectiveness were extrapolated over the patients' lifetimes with a Monte‐Carlo simulation using a Markov model, and an incremental cost‐effectiveness ratio (ICER) was computed. Indirect costs were also evaluated. Results: Among the 289 enrolled surgery candidates, 207 were operable—119 in the surgical group and 88 in the medical group—65 were not operable and not analyzed here, 7 were finally not eligible, and 10 were not followed. The proportion of patients completely seizure‐free during the last 12 months (ILAE class 1) was 69.0% in the operated group and 12.3% in the medical group during the second year (p < 0.001), and it was respectively 76.8% and 21% during the fifth year (p < 0.001). Direct costs became significantly lower in the surgical group the third year after surgery, as a result of less antiepileptic drug use. The value of the discounted ICER was 10, 406 (95% confidence interval [CI] 10, 182–10, 634) at 2 years and 2, 630 (CI 95% 2, 549–2, 713) at 5 years. Surgery became cost‐effective between 9 and 10 years after surgery, and even earlier if indirect costs were taken into account as well. Significance: Our study suggests that in addition to being safe and effective, resective surgery of epilepsy is cost‐effective in the medium term. It should therefore be considered earlier in the development of epilepsy.